Exposure to ultrafine particles and oral flora, respiratory function, and biomarkers of inflammation: A panel study in children. (15th March 2021) - Li, Hongjin; Xu, Dong; Li, Huichu; Wu, Yihan; Cheng, Yu; Chen, Zhe; Yin, Guanjin; Wang, Weidong; Ge, Yihui; Niu, Yue; Liu, Cong; Cai, Jing; et al.
Abstract: Particulate matter (PM) is the most important air pollution problem that leads to substantial health effects. However, very few studies focused on the effects of ultrafine particles (UFPs, particles< 0.1 μm) on children respiratory health. We performed a panel study with 3 rounds of follow-up among 65 pupils at the Elementary School Affiliated to Shanghai Normal University in China from November 2018 to June 2019. Real-time concentrations of UFPs were measured in the campus. In each visit, we detected biomarkers in saliva and microflora in buccal mucosa, fractional exhaled nitric oxide (FeNO) and lung function. We applied a linear mixed-effect (LME) model to examine the associations of UFPs and each health outcome. We found increased levels of FeNO and tumor necrosis factor-α (TNF-α) and reduced lung function in association with higher UFP exposure. For each interquartile range increase of UFPs, the largest changes were found in lag 0–72 h for forced vital capacity [-69.02 ml (95% CI: −114.20,  −23.84)], TNF-α [13.41 pg/ml (95% CI: 7.08, 19.73)], and FeNO [26.85% (95% CI: 11.84%, 43.88%)]. UFP exposure was associated with reduced diversity in buccal microflora with largest reduction in lag 0–72 h [12.24 (95% CI: 7.76, 16.71) for Ace index; 8.78 (95% CI: 2.96, 14.60) for Chao1 index]. UFP exposure was also associated with increased Streptococcus, Gemella, and decreased Actinomyces. Short-term UFP exposures may impair the respiratory system by inducing inflammation, decreasing lung function and attenuating buccal microbe diversity in children. Graphical abstract: Image 1 Highlights: Few epidemiological studies explored the respiratory effects of UFPs in children. Short-term UFP exposure may reduce lung function and induce airway inflammation. UFPs may increase oral inflammation and attenuate buccal microflora diversity.